2001
DOI: 10.1016/s0735-1097(01)01572-8
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular stents for coarctation of the aorta: initial results and intermediate-term follow-up

Abstract: Intravascular stent placement for native and recurrent CoA has excellent results in the short and intermediate terms. Long-term outcome remains to be evaluated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
150
3
7

Year Published

2003
2003
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 225 publications
(167 citation statements)
references
References 26 publications
7
150
3
7
Order By: Relevance
“…However a few investigators [89,91,93,108] followed more than 20 patients for more than a mean follow-up period of 2 years. In these studies the pressure gradients across the coarctation site remained low and systemic hypertension decreased in frequency and degree with consequent decrease in antihypertensive medication use.…”
Section: Follow-up Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However a few investigators [89,91,93,108] followed more than 20 patients for more than a mean follow-up period of 2 years. In these studies the pressure gradients across the coarctation site remained low and systemic hypertension decreased in frequency and degree with consequent decrease in antihypertensive medication use.…”
Section: Follow-up Resultsmentioning
confidence: 99%
“…Balloon rupture [91,93] may be prevented by avoiding curvature of the balloon/stent and use of newer stents with less injurious ends and by the use of BIB catheters. Because of the large sheath size, loss of pulse and bleeding from the puncture site has been reported.…”
Section: Complicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…4 In older patients transcatheter management with endovascular stenting is preferable to surgery in many institutions, and provides relief of pressure gradients across the coarctation site. 5 However in both circumstances patients have significant longer term risk for the development of hypertension. [6][7][8][9] Indeed, some reports claim that hypertension is the single most important long-term outcome variable in patients with repaired CoA.…”
mentioning
confidence: 99%
“…This falls into a mid-range when compared with other studies of coarctation stenting (56%-88%). 5,[8][9][10][11][12][13] As this study demonstrated, complications today are uncommon and meticulous attention to detail will continue to keep rates low. We do not support a standard dose of heparin and default to a weight-based heparin load followed by activated clotting time monitoring, and we do not use the brachial artery for a second arterial access because a randomized angioplasty trial has identified brachial access with the highest rate of complications versus radial with the lowest and femoral arterial next.…”
Section: See Article By Kische Et Almentioning
confidence: 83%